Decision-making process in Japan - Ikuko Tsukuhara Williams (Intereconomics, 1975)
As governments at last get down to business in the Tokyo Round of GATT negotiations, much is going to depend on the extent to which agreement is reached between the European Community, Japan and the United States. In this connection, it is important that people should understand the ways of the Japanese, particularly their decision-making process which somewhat seems to inhibit their ability to negotiate.
Keywords: 330; Japan